Hospital responses to the refinement of reimbursements by treatment intensity in DRG systems - Matthias Bäuml; Christian Kümpel (Health Economics, 2021)
Many OECD countries have replaced per-diem hospital reimbursement with lump sum payments by diagnosis-related groups. This study analyzes hospital responses to a large-scale refinement of reimbursement practices in Germany on January 1, 2006, in which regulating authorities introduce reimbursements by treatment intensity in the market for stroke disorder. We find that the share of admissions receiving high-intensity treatments jumps by approximately 7 percentage points around the turn of the year. At the same time, a decrease in the average clinical severity of patients receiving these high-intensity treatments reveals that the marginal high-intensity treated patient in 2006 might be less appropriate for high-intensity treatments compared to 2005. We do not find accompanying (short-term) changes in the quality of care, such as decreases in in-hospital mortality.
Keywords: 330; DRGs; hospital reimbursement; hospital supply; clinical pathways